2022
DOI: 10.1371/journal.pone.0266804
|View full text |Cite
|
Sign up to set email alerts
|

Collection of cancer Patient Reported Outcome Measures (PROMS) to link with primary and secondary electronic care records to understand and improve long term cancer outcomes: A protocol paper

Abstract: Introduction More people are living with and beyond a cancer diagnosis. There is limited understanding of the long-term effects of cancer and cancer treatment on quality of life and personal and household finances when compared to people without cancer. In a separate protocol we have proposed to link de-identified data from electronic primary care and hospital records for a large population of cancer survivors and matched controls. In this current protocol, we propose the linkage of Patient Reported Outcomes M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…UK cancer has an opportunity to deploy its unique integrated data intelligence platforms to address many of issues above. These systems of data capture and linkage enable formulation of datasets that include information on every cancer diagnosis, all hospital episodes and procedures, information on radiotherapy, surgery and SACT 114 as well as the opportunity to integrate genetic testing data, GP records and patient reported outcome measures [115][116][117][118][119] .…”
Section: Services and Systemsmentioning
confidence: 99%
“…UK cancer has an opportunity to deploy its unique integrated data intelligence platforms to address many of issues above. These systems of data capture and linkage enable formulation of datasets that include information on every cancer diagnosis, all hospital episodes and procedures, information on radiotherapy, surgery and SACT 114 as well as the opportunity to integrate genetic testing data, GP records and patient reported outcome measures [115][116][117][118][119] .…”
Section: Services and Systemsmentioning
confidence: 99%
“…Studies demonstrated that CAT was well accepted by cancer patients (as high as over 85% respondent rate) and could be performed in an efficient and timely way (completing each CAT within 2 min), and in a wide range of settings (ie, acute care setting, treatment setting, rehabilitation settings, palliative setting, patients’ homes). 21 , 49 , 50 , 51 , 52 , 53 However, it is noteworthy that different combinations of various scoring methods, item selection, and stopping rules influence both the test burden and precision. 23 , 24 The optimal algorithm can minimize the test burden and maximize precision, which is worth exploring further.…”
Section: Integration Of Proms With Computerized Adaptive Testingmentioning
confidence: 99%